Linguistic accommodation strategies in Non-Arabic speaking doctors' interactions with patients in Saudi hospitals and its role in enhancing healthcare for them - Lamouchi, Ali; Mohamed Sayed Abdellatif; Hafez, Waheed Elsayed (Research Journal in Advanced Humanities, 2024)
From a sustainable development perspective in healthcare settings, the quality of communication between healthcare professionals and patients is crucial. The purpose of this exploratory descriptive analysis was to examine the communication strategies used by some non-Arabic speaking physicians in Saudi Arabia hospitals when communicating with their patients. Communication Accommodation Theory (CAT) was used as the framework for this study. Eight medical doctors were audiotaped, and the recordings were transcribed verbatim and coded by the researchers for the five a priori defined sociolinguistic communication adjustment strategies in CAT: 1) approximation; 2) interpretation; 3) discourse management 4) emotional; and 5) interpersonal strategies. The findings reveal that all doctors use convergence accommodation strategies. They focus mainly on approximation strategies where they pay great attention essentially to the quality of their language. It is recommended that this study be followed by a larger scale research.